System of evaluation of integrative projects (sepi): analysis for its implementation in the Corporacion Universitaria Americana - Mauricio Ortiz, Frank; García Arango, David Alberto; Mauricio Ortiz, Frank; García Arango, David Alberto; Mauricio Ortiz, Frank; García Arango, David Alberto (Corporación universitaria Americana, 2021)
This article refers to an applied research project that aims to evaluate the integrative projects of the engineering faculty of the CORPORACION UNIVERSITARIA AMERICANA. The data was obtained from the same university seeking to solve in a practical way through a web platform the results management of the Project-Based Learning Strategy of the Faculty of Engineering. This platform is capable of processing the information related to the different search topics. In addition to providing information; It also has a grading system where teachers and students canobserve the corrections and progress or declarations of their projects. The implications of implementing an information system are presented to solve the problems that have to do with the evaluation of integrative projects corresponding to the faculty of systems engineering and industrial engineering within the CORPORACION UNIVERSITARIA AMERICANA(CUA).